(untitled) (Jóvenes en la Ciencia, 2025)
This research paper analyzes the influence of an accelerating admixture on concrete properties, specifically its setting time and compressive strength. The inclusion of these admixtures is a common practice in the construction industry to optimize construction times, especially in conditions requiring rapid setting or working at low temperatures. The study will investigate how these admixtures modify cement hydration kinetics, directly influencing early strength gain and the final strength of the material. The results are compared with those obtained from cylinders without an accelerating admixture.